Study of Rape Cases Recorded at a Tertiary Care Hospital in Bangladesh (Journal of Shaheed Suhrawardy Medical College, 2017)
Background: Rape is a global problem. Epidemiology of Rape differs from country to country.Objective: This study was carried out to determine the incidence of Rape Cases in tertiary care hospital in Bangladesh.Methodology: This retrospective study was conducted on the characteristics of the rape cases reported in the Department of Forensic Medicine at Dinajpur Medical College from January 2005 to December 2007. Cases were examined by taking the proper papers from the legal authority. All the cases were eferred form 13th Police station of Dinajpur District, Dinajpur.Result: A total number of 300 cases were collected in this study. The overall cases of rape were 2.3%. More detailed data from 300 cases reveals that 2/3 of the cases were in the age group of 14 to 20 years. Consider the socio- economics status of the victim, it is found that the highest frequency of rape is within the lowest socio-economic group.Conclusion: In the conclusion, the study reveals that the majority of the rape cases were in lower social-economic group with an age 15 to 18 years.J Shaheed Suhrawardy Med Coll, 2014; 6(2):64-66